Improving the economic efficiency of grain transportation - Khairullin, B.T.; Derman, A.L. (BUKETOV BUSINESS REVIEW, 2024)
Object: solving the problem of increasing the economic efficiency of grain transportation by rail. The solution to this problem involves the use of mathematical methods of analysis. Method: mathematical method of linear programming. Comparative analysis. The analysis of the current state of the organization of transportation of mass cargo by rail was performed. A graphical analysis of the costs of transportation work of rail transport during mass transportation of grain was performed. Results: solutions to logistic problems in the transportation of goods by rail, which allow to obtain a huge eco nomic effect comparable to the cost of the transported goods. Comparison of costs for the transportation of grain ac cording to the plan compiled by the transportation department of Kazakhstan Temir Zholy taking into account customers and according to the plan obtained using the mathematical method, the potential method, shows how much it is possible to reduce costs during transportation. Conclusions: The proposed method for calculating transportation plans using computer programs will significantly reduce the cost of transportation. Modernization of rail transport is necessary. The wagon fleet needs to be updated. New railway lines and cargo terminals with digitalization of cargo operations need to be built. The method for calculating the optimal transportation plan can be used when planning the transportation of bulk cargo.